The increase of dairy intake is the main dietary factor associated with reduction of body weight in overweight adults after lifestyle change program - Prado de Oliveira, Erick; Mourão Diegoli, Ana Carolina [UNESP]; Corrente, José Eduardo [UNESP]; Portero McLellan, Kátia Cristina [UNESP]; Burini, Roberto Carlos [UNESP] (Aula Medica, 2015)
This study evaluated which was the main nutritional change associated with weight reduction of overweight adult participants of a lifestyle change program. It was hypothesized that increases in dairy intake could be an important nutrition intervention in a lifestyle change program. 117 individuals, male (19.5%) and female (80.5%), with a minimum age of 36 years (54.2 ± 10.4). All study participants were enrolled in a lifestyle change program consisting of nutritional counseling and physical activity during 20 weeks. All participants were grouped in three groups according to Body Mass Index (BMI) delta median (-0.87 kg/m2) of individuals that showed weight loss: G1 - lost more than 0.87 kg/m2 of BMI (n = 38); G2 - lost 0 to 0.87 kg/m2 of BMI (n = 36); and G3 - increased BMI (n = 43). G1 increased dairy, fruit and vegetables intake and after forward stepwise multiple regression analysis, it was noted that an increase in dairy product intake of 0.40 servings per day had an impact of 9.6% on the loss of one kg/m2 of BMI. In conclusion, an increase in dairy product intake was the main dietary factor associated with reductions in body weight in overweight adults after 20 weeks of lifestyle change program.
Keywords: Obesity; Dairy products; Intervention; Diet; Lifestyle